The measurement of the plane strain fracture toughness (KIC) of polymethyl - methacrylate - 330879 Chan, Kien Ming (Sekudai : Universiti Teknologi Malaysia, 1989)
Thesis (Bachelor of Mechanical Engineering) - Universiti Teknologi Malaysia, 1989